I tre artefici della Rivoluzione d'ottobre (Lenin, Trotzki, Stalin) - Wolfe, Bertram D. (Firenze : La nuova Italia, 1953)
Fonds Perrone
Italiaans
Monografie
Keywords: Lenin, Vladimir; Trotski, Leon; Stalin, Jozef; Russische revolutie